Human dignity and the right to culture - Watermeyer, Natalie (My University, 2008)
In this report I examine how, and to what extent, the value of human dignity upon which the South African Constitution is founded supports a right to culture. I consider two views as to the nature of human dignity. In chapter two, I look at the Kantian approach, which locates a person’s humanity – and therefore dignity – in her capacity for rational autonomy. In chapter three I argue for Martha Nussbaum’s broader view that there are certain capabilities that constitute “humanity” – for example “senses, imagination and thought”, emotions, and the capacity for affiliation – that are fundamental to any fully human life. I then examine to what extent a right to culture is supported by this view of human dignity, using several case studies set out in chapter four. In chapters five and six I look at the arguments for cultural rights put forward by Will Kymlicka and Charles Taylor in the light of Nussbaum’s approach; in chapter seven I sketch out further possible arguments for this right based upon the capacities for emotion and affiliation. Finally, in chapter eight I conclude that while appeal to human dignity provides several avenues of support for a high level right to culture, as often as not these also provide equally good reasons to oppose one. Thus respect for human dignity requires that each case be considered on its own merits.